2021
DOI: 10.1177/23259671211032229
|View full text |Cite
|
Sign up to set email alerts
|

Interrater Reliability of the Prone Apprehension Relocation Test

Abstract: Background: The Prone Apprehension Relocation Test (PART) augments existing radiographic measures and clinical provocative maneuvers in diagnosing hip instability. One measure of the potential clinical utility of the PART depends on the reproducibility of test results by evaluating providers including physicians, licensed athletic trainers, and physical therapists. Purpose: To determine the interrater reliability of the PART among health care providers. Study Design: Cohort study (diagnosis); Level of evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Thus, there is a bias with regard of the interpretation and assessability of the PART result. However, a recent study demonstrated a high inter- and intraobserver reliability regarding the PART interpretation [ 19 ], so that we consider this bias as low. It should also be noted that the study was performed in a high-volume center, so that a high number of dysplastic hips were included in the patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is a bias with regard of the interpretation and assessability of the PART result. However, a recent study demonstrated a high inter- and intraobserver reliability regarding the PART interpretation [ 19 ], so that we consider this bias as low. It should also be noted that the study was performed in a high-volume center, so that a high number of dysplastic hips were included in the patient population.…”
Section: Discussionmentioning
confidence: 99%
“…A very recently described clinical test for the detection of hip instability is the Prone Apprehension Relocation Test (PART) [ 18 , 19 ]. A correlation between anterior undercoverage detected by computed tomography (CT) and a positive Part was demonstrated, as PART-positive patients had significantly more acetabular anteversion at the 3 o’clock position [ 18 ].…”
Section: Introductionmentioning
confidence: 99%